The Ambition of Fieldwork - George E. Marcus (Terrains/Théories)
In this interview of April 2016, the American anthropologist George Marcus comes back on his academic trajectory in order to enlighten the genesis of the 1995 article on multi-sited ethnography. This particular approach is to be understood less as a tool to analyse globalization per se than as a critical perspective finding its rationale within the history of anthropology. He also insists on his more recent works about the epistemology and methodology of anthropology, as well as on the future of fieldwork and the relation between fieldwork and theory in this discipline.